Analisis Kohesi Gramatikal pada Debat Calon Wakil Presiden Tahun 2024 sebagai Bahan Ajar Bahasa Indonesia - Ramadhan, Deri; Maulana, Nanang; Purlilaiceu, Purlilaiceu (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
This study aims to describe the use of Grammatical Cohesion contained in the vice presidential candidate debate in 2024 and its utilization as teaching material in high school. This research was conducted using descriptive method with the research object of the 2024 vice presidential candidate debate. The data collection techniques used were documentation study techniques and content analysis. Data analysis techniques are data reduction, data presentation, conclusion and verification. Based on the results of the analysis, 25 reference devices, 6 substitution devices, 20 conjunction devices were found. Each of these Grammatical Cohesion elements has a very important role because it can create sentences that are interrelated with one another, so that listeners better understand every message conveyed in the debate. The findings can provide deep insight for students about the use of cohesion in oral communication, so as to improve students' ability to understand texts, besides that the findings of this study can be utilized as the development of teaching materials that are more interactive and contextual. The vice presidential candidate debate event analyzed for the use of grammatical cohesion can be used as an example in teaching materials, so that these learning activities can encourage students to practice making cohesive sentences in oral discourse skills, one of which is in a debate.